Are labor regulations driving computer usage in India's retail stores ? - Amin, Mohammed (The World Bank, 2007)
A recent survey of 1,948 retail stores in India conducted by the World Bank's Enterprise Surveys shows that 19 percent of the stores use computers for their business. In some states like Kerala, computer use is as high as 40 percent. Using this data the author finds labor regulation as an important determinant of computer use. His estimates suggest that when faced with burdensome labor regulations, the probability of using a computer rises by over 36 percentage points for an average store. These findings formally confirm a commonly held but untested view that labor regulation may be responsible for the spread of labor saving modern technology